TEACHER AND STUDENT’S DIFFICULTIES IN WRITING RECOUNT TEXT USING PICTURE SERIES - Aseptiana Parmawati; Astri Aggraeni (IKIP Siliwangi, 2022)
Writing is one of the problems that students and teachers often have. Because writing was difficult to learned and taught for some students. One method that can be used in teaching writing was Picture Series. The research was conducted in SMP YPKKP in Bandung. the research aimed to identify teacher and student’s difficulties in writing recount text using Picture Series at eigth grade. This research used descriptive qualitative research. From the result, the difficulty of teachers and students in teaching and learning writing using picture series is that students were not optimal in made texts and they difficulty to developing their ideas because of their limited knowledge in vocabulary, then they did not master grammar and their lack of understanding of changed in verbs used in making recount text. As a result, they will write according to their modest abilities. Therefore, teachers have to often provide motivation to students in the classroom or outside the school environment regardless of the burden of their responsibilities as teachers, and must be more optimal and creative in teaching by using various methods, one of which is using a picture series, the purpose is to improve students' writing skills. Keywords: Recount Text, Writing, Picture Series